Leadership unleashed: Fuelling or failing at retaining women in higher education - Mariette Coetzee; Maryam Moosa (SA Journal of Human Resource Management)
Orientation: Higher education institutions face significant challenges in retaining women’s services as they navigate the challenges of a career. One of the factors critical in retaining the services concerns leadership behaviour displayed by managers.